2015
DOI: 10.1016/j.ic.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

On labeled birooted tree languages: Algebras, automata and logic

Abstract: With an aim to developing expressive language theoretical tools applicable to inverse semigroup languages, that is, subsets of inverse semigroups, this paper explores the language theory of finite labeled birooted trees: Munn's birooted trees extended with vertex labeling. To this purpose, we define a notion of finite state birooted tree automata that simply extends finite state word automata semantics. This notion is shown to capture the class of languages that are definable in Monadic Second Order Logic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…It has already been observed that an adequate algebraic theory for inverse monoid morphisms can be developed by means of certain kind of premorphisms instead of morphisms [9,10,12,14]. As a matter of fact, transition monoids of walking automata induce a different type of premorphisms that could also be investigated as new language recognizers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been observed that an adequate algebraic theory for inverse monoid morphisms can be developed by means of certain kind of premorphisms instead of morphisms [9,10,12,14]. As a matter of fact, transition monoids of walking automata induce a different type of premorphisms that could also be investigated as new language recognizers.…”
Section: Resultsmentioning
confidence: 99%
“…Taking the group defined from A = {a, b, c, d} by cc = 1, dd = 1 and cd = 0, we obtain vertex-labeled birooted trees with edges labeled by a or b and, following Remark 5, vertices labeled over P({c, d}). Thanks to the axiom cd = 0, only the birooted graph encoding zero has a vertex labeled by both c and d. The language theory of these vertex-labeled birooted graphs has been studied in [10,14].…”
Section: Remark 18mentioning
confidence: 99%
“…Although not much popular even in theoretical computer science, it is known that their free algebras capture deterministic unranked trees [13]. They have recently been studied in formal language theory by the second author for developing a new algebraic characterization of regular languages of finite trees [11]. It is conjectured that dropping the commutation hypothesis (property (8)) will eventually lead to languages of ranked trees.…”
Section: Related Workmentioning
confidence: 99%